Substitusi Medium Sintetik dengan Pupuk Daun, Air Kelapa dan Ekstrak Nabati pada Subkultur Anggrek Cattleya pastoral Innocence secara In Vitro - Handayani, Etty; Isnawan, Bambang Heri (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2014)
A research was perfomed to find the proper of coconut water and natural ekstracts combined with Hyponex medium that compared with Vacin & Went medium. This research has been done at Tissue Culture Laboratory, Agricultural Faculty, Universitas Muhammadiyah Yogyakarta. The method of this research was arranged in Randomized Complete Design with 9 treatments and 8 replications. The treatments were VW + NAA 0,5 ppm + BAP 3 ppm, green Hyponex 3 g/l, green Hyponex 3 g/l + bean sprouts 150 g/l, green Hyponex 3 g/l + tomatoes 150 ml/l, green Hyponex 3 g/l + avocado 150 g/l, red Hyponex 3 g/l, red Hyponex 3 g/l + bean sprouts 150 g/l, red Hyponex 3 g/l + tomatoes 150 ml/l, red Hyponex 3 g/l + avocado 150 g/l. The each of Hyponex mediums were given with bananas 150 g/l and coconut water 150 ml/l. The result of this research showed that Hyponex mediums combined with natural ekstract was not signicicantly with Vacin & Went medium to high and shoot growth. Red Hyponex medium 3 g/l combined bananas 150 g/l and coconut water 150 ml/l resulted the best high, leaf and shoot in tissue culture Cattleya pastoral innocence orchid.